Back and Forth

A simple pendulum comprising of a mass m m attached to an inextensible, massless string of length l l is released from an angle of θ \theta .

Let T = f ( θ ) T=f\left(\theta\right) be the time period of the pendulum and let T 0 = 2 π l g T_0=2\pi\sqrt{\frac{l}{g}} .

Find lim θ 0 [ ( 2 θ ) 4 ( T T 0 1 ) 1 θ 2 ] . \displaystyle\lim_{\theta\to 0}\left[\left(\dfrac{2}{\theta}\right)^4\left(\dfrac{T}{T_0}-1\right)-\dfrac{1}{\theta^2}\right].

7 180 \dfrac{7}{180} 11 192 \dfrac{11}{192} 13 196 \dfrac{13}{196} 17 204 \dfrac{17}{204}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Guilherme Niedu
Sep 8, 2018

Again I will post a long, detailed solution, showing all steps. It can be boring, but I like to detail these things :)

Let α \alpha be the angle the pendulum makes with the veritical at any given time. Also, let h h be the difference in height bewteen the pendulum when its angle is α \alpha and when its angle is θ \theta (the initial value). Also, let v v be its initial linear velocity and let m m be its mass.

The change in kinetic energy must be the same as the change in potential energy. That is:

m g h = m v 2 2 \large \displaystyle mgh = \frac{mv^2}{2}

v = 2 g h \large \displaystyle v = \sqrt{2gh}

The linear velocity is equal to l l times the angular velocity:

l d α d t = 2 g h \large \displaystyle l \frac{d \alpha}{dt} = \sqrt{2gh}

Since the vertical distance from the pendulum to its fixed suspension point is l cos ( α ) l \cos(\alpha) for any angle α \alpha it makes with the vertical, the change in height will be equal to l cos ( α ) l cos ( θ ) l \cos(\alpha) - l \cos(\theta) :

d α d t = 2 g l [ cos ( α ) cos ( θ ) ] \large \displaystyle \frac{d \alpha}{dt} = \sqrt{ \frac{2g}{l} [ \cos(\alpha) - \cos(\theta) ] }

Or:

d t d α = l 2 g 1 cos ( α ) cos ( θ ) \large \displaystyle \frac{dt}{d \alpha} = \sqrt{ \frac{l}{2g} \cdot \frac{1}{ \cos(\alpha) - \cos(\theta) } }

d t = l 2 g 1 cos ( α ) cos ( θ ) d α \large \displaystyle \int dt = \int \sqrt{ \frac{l}{2g} \cdot \frac{1}{ \cos(\alpha) - \cos(\theta) } } d \alpha

Since its movement is θ 0 θ 0 θ \theta \rightarrow 0 \rightarrow -\theta \rightarrow 0 \rightarrow \theta again, we can simply conisder 4 4 times the integral between 0 0 and θ \theta :

T = 4 l 2 g 0 θ 1 cos ( α ) cos ( θ ) d α \large \displaystyle T = 4\ \sqrt{ \frac{l}{2g} } \int_0^{\theta} \frac{1}{ \sqrt{ \cos(\alpha) - \cos(\theta) } } d \alpha

If we make

u = arcsin ( sin ( α 2 ) sin ( θ 2 ) ) \large \displaystyle u = \arcsin \left ( \frac{ \sin \left ( \frac{\alpha}{2} \right ) } { \sin \left ( \frac{\theta}{2} \right ) } \right )

Then:

d u = 1 1 ( sin ( α 2 ) sin ( θ 2 ) ) 2 cos ( α 2 ) sin ( θ 2 ) 1 2 d α \large \displaystyle du = \frac{1}{\sqrt{1 - \left ( \frac{ \sin \left ( \frac{\alpha}{2} \right ) } { \sin \left ( \frac{\theta}{2} \right ) } \right )^2 }} \cdot \frac{ \cos \left ( \frac{\alpha}{2} \right ) } { \sin \left ( \frac{\theta}{2} \right ) } \cdot \frac12 d \alpha

d u = cos ( α 2 ) 2 sin ( θ 2 ) 2 2 sin ( α 2 ) 2 1 2 d α \large \displaystyle du = \frac{\cos\left( \frac{\alpha}{2} \right)}{ \sqrt{2 \sin \left ( \frac{\theta}{2} \right )^2 - 2 \sin \left ( \frac{\alpha}{2} \right )^2 } } \frac{1}{\sqrt{2}} d \alpha

Since cos ( 2 x ) = 1 2 sin 2 ( x ) \cos(2x) = 1 - 2\sin^2(x) :

d u = 1 sin 2 ( α 2 ) cos ( α ) cos ( θ ) 1 2 d α \large \displaystyle du = \frac{\sqrt{ 1 - \sin^2 \left( \frac{\alpha}{2} \right)}}{\sqrt{\cos(\alpha) - \cos(\theta)}} \frac{1}{\sqrt{2}} d \alpha

d u = 1 sin 2 ( θ 2 ) sin 2 ( u ) cos ( α ) cos ( θ ) 1 2 d α \large \displaystyle du = \frac{\sqrt{ 1 - \sin^2 \left( \frac{\theta}{2} \right) \sin^2 (u) }}{\sqrt{\cos(\alpha) - \cos(\theta)}} \frac{1}{\sqrt{2}} d \alpha

d α = 2 cos ( α ) cos ( θ ) 1 sin 2 ( θ 2 ) sin 2 ( u ) d u \large \displaystyle d \alpha = \sqrt{2} \frac{\sqrt{\cos(\alpha) - \cos(\theta)}}{\sqrt{ 1 - \sin^2 \left( \frac{\theta}{2} \right) \sin^2 (u) }} du

So, the period becomes:

T = 4 l g 0 π 2 1 1 sin 2 ( θ 2 ) sin 2 ( u ) d u \large \displaystyle T = 4\ \sqrt{ \frac{l}{g} } \int_0^{\frac{\pi}{2}} \frac{1}{\sqrt{1 - \sin^2(\frac{\theta}{2}) \sin^2(u) }} du

This is a Complete elliptic integral of the first kind with k = sin ( θ 2 ) k = \sin(\frac{\theta}{2}) . Using Legendre polynomials until the term of order 4 4 (since on the limit the highest term has order 4 4 ):

T = 2 π l g [ 1 + 1 4 sin 2 ( θ 2 ) + 9 64 sin 4 ( θ 2 ) + O ( sin 6 ( θ 2 ) ) ] \large \displaystyle T = 2 \pi \sqrt{\frac{l}{g}} \left [ 1 + \frac14 \sin ^2\left ( \frac{\theta}{2} \right ) + \frac{9}{64} \sin ^4\left ( \frac{\theta}{2} \right ) + \mathcal{O} \left ( \sin ^6\left ( \frac{\theta}{2} \right ) \right ) \right ]

Using the Maclaurin series for sine, and again computing until the term of order 4 4 (since on the limit the highest term has order 4 4 ):

T = T 0 [ 1 + 1 16 θ 2 + 11 3072 θ 4 + O ( θ 6 ) ] \color{#20A900} \boxed{ \large \displaystyle T = T_0 \left [ 1 + \frac{1}{16} \theta^2 + \frac{11}{3072} \theta^4 + \mathcal{O} \left ( \theta^6 \right ) \right ] }

Now, to the limit:

L = lim θ 0 [ ( 2 θ ) 4 ( T T 0 1 ) 1 θ 2 ] \large \displaystyle L = \lim_{\theta \rightarrow 0} \left [ \left ( \frac{2}{\theta} \right ) ^4 \left ( \frac{T}{T_0} - 1 \right ) - \frac{1}{\theta^2} \right ]

L = lim θ 0 [ ( 16 θ 4 ) ( 1 + 1 16 θ 2 + 11 3072 θ 4 + O ( θ 6 ) 1 ) 1 θ 2 ] \large \displaystyle L = \lim_{\theta \rightarrow 0} \left [ \left ( \frac{16}{\theta^4} \right ) \left ( 1 + \frac{1}{16} \theta^2 + \frac{11}{3072} \theta^4 + \mathcal{O} \left ( \theta^6 \right ) - 1 \right ) - \frac{1}{\theta^2} \right ]

L = lim θ 0 [ 1 θ 2 + 11 192 + O ( θ 2 ) 1 θ 2 ] \large \displaystyle L = \lim_{\theta \rightarrow 0} \left [ \frac{1}{\theta^2} + \frac{11}{192} + \mathcal{O} \left ( \theta^2 \right ) - \frac{1}{\theta^2} \right ]

L = lim θ 0 [ 11 192 + O ( θ 2 ) ] \large \displaystyle L = \lim_{\theta \rightarrow 0} \left [ \frac{11}{192} + \mathcal{O} \left ( \theta^2 \right ) \right ]

L = 11 192 \color{#3D99F6} \boxed{\large \displaystyle L = \frac{11}{192} }

Mark Hennings
Sep 8, 2018

If, in general, the pendulum subtends an angle α \alpha with the downwards vertical, after starting from rest when α = θ \alpha = \theta , then conservation of energy tells us that 1 2 m 2 α ˙ 2 + m g ( 1 cos α ) = m g ( 1 cos θ ) \tfrac12m \ell^2 \dot{\alpha}^2 + mg\ell(1 - \cos\alpha) \; = \; mg\ell(1 - \cos\theta) so that α ˙ 2 = 2 g ( cos α cos θ ) \dot{\alpha}^2 \; = \; \tfrac{2g}{\ell}(\cos\alpha - \cos\theta) and so the period of oscillation is T ( θ ) = 4 2 g 0 θ d α cos α cos θ = 2 g 0 θ d α sin 2 1 2 θ sin 2 1 2 α T(\theta) \; = \; 4\sqrt{\tfrac{\ell}{2g}} \int_0^\theta \frac{d\alpha}{\sqrt{\cos\alpha - \cos\theta}} \; = \; 2\sqrt{\tfrac{\ell}{g}} \int_0^\theta \frac{d\alpha}{\sqrt{\sin^2\frac12\theta - \sin^2\frac12\alpha}} The substitution sin 1 2 α = sin 1 2 θ sin u \sin\tfrac12\alpha = \sin\tfrac12\theta \sin u gives T ( θ ) = 2 π T 0 0 1 2 π d u 1 sin 2 1 2 θ sin 2 u = 2 π T 0 K ( sin 2 1 2 θ ) T(\theta) \; = \; \tfrac{2}{\pi}T_0 \int_0^{\frac12\pi} \frac{du}{\sqrt{1 - \sin^2\frac12\theta \sin^2u}} \; = \; \tfrac{2}{\pi}T_0 K\big(\sin^2\tfrac12\theta\big) where K K is the complete elliptic integral of the first kind. Now it is a standard result that K ( m ) = 1 2 π [ 1 + ( 1 2 ) 2 m + ( 1 3 2 4 ) 2 m 2 + ] m < 1 K(m) \; = \; \tfrac12\pi\left[1 + \big(\tfrac{1}{2}\big)^2 m + \big(\tfrac{1 \cdot 3}{2 \cdot 4}\big)^2m^2 + \cdots \right] \hspace{2cm} |m| < 1 so that 2 π K ( m ) 1 + 1 4 m + 9 64 m 2 + o ( m 2 ) m 0 \tfrac{2}{\pi}K(m) \; \sim \; 1 + \tfrac14m + \tfrac{9}{64}m^2 + o(m^2) \hspace{2cm} m \to 0 so that T ( θ ) T 0 1 + 1 4 sin 2 1 2 θ + 9 64 sin 4 1 2 θ + o ( θ 4 ) 1 + 1 4 ( 1 2 θ 1 48 θ 3 ) 2 + 9 64 × 1 16 θ 4 + o ( θ 4 ) 1 + 1 16 θ 2 + 11 3072 θ 4 + o ( θ 4 ) \begin{aligned} \tfrac{T(\theta)}{T_0} & \sim \; 1 + \tfrac14\sin^2\tfrac12\theta + \tfrac{9}{64}\sin^4\tfrac12\theta + o(\theta^4) \\ & \sim \; 1 + \tfrac14\big(\tfrac12\theta - \tfrac{1}{48}\theta^3\big)^2 + \tfrac{9}{64} \times \tfrac{1}{16}\theta^4 + o(\theta^4) \\ & \sim \; 1 + \tfrac{1}{16}\theta^2 + \tfrac{11}{3072}\theta^4 + o(\theta^4) \end{aligned} as θ 0 \theta \to 0 , and hence ( 2 θ ) 4 ( T ( θ ) T 0 1 ) 1 θ 2 = 11 192 + o ( 1 ) θ 0 \left(\tfrac{2}{\theta}\right)^4\left(\tfrac{T(\theta)}{T_0} - 1\right) - \tfrac{1}{\theta^2} \; = \; \tfrac{11}{192} + o(1) \hspace{2cm} \theta \to 0 so that lim θ 0 [ ( 2 θ ) 4 ( T ( θ ) T 0 1 ) 1 θ 2 ] = 11 192 \lim_{\theta \to 0}\left[ \left(\tfrac{2}{\theta}\right)^4\left(\tfrac{T(\theta)}{T_0} - 1\right) - \tfrac{1}{\theta^2}\right] \; = \; \boxed{\tfrac{11}{192}}

We posted the same solution at the same time! Haha

Guilherme Niedu - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...